Control of Tissue Fibrosis by 5-Methoxytryptophan, an Innate Anti-Inflammatory Metabolite - Wu, Kenneth K (Frontiers in Pharmacology, 2021)
Tissue fibrosis causes debilitating human diseases such as liver cirrhosis, heart failure, chronic kidney disease and pulmonary insufficiency. It is a dynamic process orchestrated by specific subsets of monocyte-macrophages, fibroblasts, pericytes and hepatic stellate cells. Fibrosis is linked to tissue inflammation. Pro-inflammatory macrophages promote fibrosis by driving myofibroblast differentiation and macrophage myofibroblast transition. Myofibroblasts express α-smooth muscle cell actin (α-SMA) and secrete extracellular matrix (ECM) proteins notably collagen I and III. Deposition of ECM proteins at injury sites and interstitial tissues distorts normal structure and impairs vital functions. Despite advances in the mechanisms of fibrosis at cellular, molecular and genetic levels, prevention and treatment of fibrotic diseases remain poorly developed. Recent reports suggest that 5-methoxytryptophan (5-MTP) is effective in attenuating injury-induced liver, kidney, cardiac and pulmonary fibrosis. It inhibits macrophage activation and blocks fibroblast differentiation to myofibroblasts. Furthermore, it inhibits hepatic stellate cell differentiation into myofibroblasts. As 5-MTP is an endogenous molecule derived from tryptophan catabolism via tryptophan hydroxylase pathway, it is well-suited as a lead compound for developing new anti-fibrotic drugs. This article provides an overview of 5-MTP synthesis, and a critical review of its anti-fibrotic activities. Its mechanisms of actions and potential therapeutic value will be discussed.